2020
DOI: 10.3390/v12111262
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genome Sequence Analysis of Porcine Astroviruses Reveals Novel Genetically Diverse Strains Circulating in East African Smallholder Pig Farms

Abstract: Astroviruses (AstVs) are widely distributed and are associated with gastroenteritis in human and animals. The knowledge of the genetic diversity and epidemiology of AstVs in Africa is limited. This study aimed to characterize astroviruses in asymptomatic smallholder piglets in Kenya and Uganda. Twenty-four samples were randomly selected from a total of 446 piglets aged below 6 months that were initially collected for rotavirus study and sequenced for whole genome analysis. Thirteen (13/24) samples had contigs … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…MHC I processing (this tool combines predictors of proteasomal processing, TAP transport and MHC binding to produce an overall score for each peptides potential of being a T cell epitope). Based on this overall score, six best epitopes were selected for further evaluation (Zhang et al 2015 ; Amimo et al 2020 ). The degree of similarity between the epitope and the target (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MHC I processing (this tool combines predictors of proteasomal processing, TAP transport and MHC binding to produce an overall score for each peptides potential of being a T cell epitope). Based on this overall score, six best epitopes were selected for further evaluation (Zhang et al 2015 ; Amimo et al 2020 ). The degree of similarity between the epitope and the target (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…This was confirmed by Clustal omega, an algorithm of multiple amino acid sequence alignment available at ( http://www.ebi.ac.uk/Tools/msa/Clustalo ). BLAST search was used to assemble the sequences of antigen reported for different serotypes (Zhang et al 2015 ; Amimo et al 2020 ). The resulting consensus sequence would characterize all of the virus’s major serotypes.…”
Section: Methodsmentioning
confidence: 99%
“…In members of the genus Mamastrovirus , experimental evidence has previously inferred the presence of a VPg linked to infectious viral RNA, and in human astrovirus, this has been shown to be essential for in vitro infectivity [ 36 , 45 , 46 ]. In this study we identified a conserved polyprotein within the ORF1ab of USA PoAstV3 strains spanning between previously described cleavage sites encompassing the putative human astrovirus VPg.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the PoAstV3 sequences obtained in this study, 14 more PoAstV3 strains from the USA (GenBank accession number: JX556691, KY940545, MT394895, MT394896), Europe (GenBank accession number: MK962341, MK962342, KY073229, KY073231, KY073232), and Japan (GenBank accession number: LC201595, LC201596, LC201597, LC201598, LC20159) were retrieved to compare intrinsic PoAstV3 features. Mamastrovirus 3 GER/L00919-K17/2014 (LT898424), which was previously identified in other studies to cluster closely to PoAstV3 strains was also included in the analysis [ 45 , 46 ]. All sequences were retrieved from GenBank.…”
Section: Methodsmentioning
confidence: 99%
“…PAstV2 and PAstV4 were detected from the blood and fecal samples, causing viremia and circulate in pig herds (19). It is worth noting that genetic recombination events among PAstVs or other astrovirus species were frequently reported, which may contribute to the genetic diversity and evolution of PAstVs (19)(20)(21)(22)(23)(24). Multiple genotypes of PAstV coinfections will further accelerate the genetic variation of this virus and bring challenges to the monitoring of PAstVs.…”
Section: Introductionmentioning
confidence: 99%